1995
DOI: 10.1101/gad.9.13.1598
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CD36 as the first gene dependent on the B-cell differentiation factor Oct-2.

Abstract: The Oct-2 transcription factor is expressed predominantly in B lymphocytes and has been shown previously to be important for the terminal phase of B-cell differentiation in mice. A number of genes specifically expressed in B cells contain Oct-2-binding sites in their regulatory regions. However, the analysis of expression levels of these genes in Oct-2-deficient B cells revealed that they were unaffected. Hence, there were no genes known that critically depend on Oct-2 for their expression. To understand the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 59 publications
0
52
0
Order By: Relevance
“…In addition to the minor populations of FO B cells that express CD36, it was also expressed at a slightly lower level on most MZ precursors and a subset of transitional B cells, suggesting that these cells may be activated. CD36 expression along with other MZ B cell markers such as CD9 and FcRL5 may be indicative of activation signals involved in the (41) showed that CD36 expression is strictly regulated by Oct2 in B cells. Thus, it will also be of interest to check Oct2 expression by B cell subsets.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the minor populations of FO B cells that express CD36, it was also expressed at a slightly lower level on most MZ precursors and a subset of transitional B cells, suggesting that these cells may be activated. CD36 expression along with other MZ B cell markers such as CD9 and FcRL5 may be indicative of activation signals involved in the (41) showed that CD36 expression is strictly regulated by Oct2 in B cells. Thus, it will also be of interest to check Oct2 expression by B cell subsets.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Western blot analysis was carried out according to previously published protocols. 16,18 Cell culture and transfection For electroporation, 5 ϫ 10 6 cultured cells were pelleted and resuspended in a final volume of 300 L RPMI medium supplemented with 10% FCS. Fifteen micrograms of the respective luciferase reporter plasmid (details about the wild-type immunoglobulin octamer enhancer and the synthetic multimerized octamer reporter constructs can be found in Laumen et al 12 and Pfisterer et al 19,20 ) were added to the cells.…”
Section: Northern and Western Blot Analysesmentioning
confidence: 99%
“…In agreement with this idea the immunoglobulin enhancer exhibits a dramatically reduced activity in B cells lacking Oct-2 (6), and knockout mice lacking a functional Oct-2 gene show defects in B cell maturation and response to antigen (7). Moreover, these knockout mice also exhibit a lack of CD36 expression in their B lymphocytes, identifying the gene encoding this factor as another target for activation by Oct-2 in B lymphocytes (8).…”
mentioning
confidence: 52%